A transparent soil modeling approach for investigating the performance of geosynthetic-encased granular columns in soft soils - Lima, A. M. P. V.; Portelinha, F. H. M. (Frontiers in Built Environment, 2026)
Laboratory-scale physical modeling has established itself as an effective technique for investigating mechanisms underlying geotechnical problems. Recently, the use of transparent materials, combined with advances in digital imaging technologies, has emerged as an innovative and non-invasive approach for analyzing soil behavior. Transparent soils are biphasic systems composed of translucent solid particles and saturating fluids with closely matched refractive indices, enabling clear observation of internal processes. Digital Image Correlation (DIC) has proven particularly effective when integrated with transparent soil models. As a non-contact optical method, DIC minimizes interference and measurement inaccuracies associated with traditional instrumentation, allowing more reliable interpretation of displacement and strain fields. Recent studies have increasingly focused on transparent soils for modeling geosynthetic-reinforced soil structures. In this work, the behavior of embankments constructed over soft soils improved with geosynthetic-encased granular columns (GECs) was investigated using stratified transparent soil models. The study evaluated the mechanisms of load transfer from the embankment to the columns, as well as resulting deformations and differential settlements. Transparent soil modeling allowed observation of key load transfer mechanisms, such as soil arching within the PTC, and enabled evaluation of the soil arching ratio. Overall, transparent soil modeling proved to be a suitable and effective technique for simulating this type of geotechnical system, providing valuable insights into its behavior.